The level of awareness of solid waste management of elected officials in the Municipality of Bugasong, Antique - Pancubila, Ricardo S.; Sumbilla, Jeffrey; Bangcaya, Neil P. (2005)
This study primarily aims to determine the level of awareness of elected local officials in the Municipality of Bugasong. The respondents of the study are the elected local officials in the municipality of Bugasong, Antique. Data was obtained through a questionnaire in this study and statistical tool was also applied to tabulate the data presented. The study found out that the Elected Local Officials in the Municipality of Bugasong are less aware of the solid Waste Management particularly the presence of the R.A. 9003 other wise known as the Ecological Waste Management Act of 2000. In view of the findings, it is highly recommended that the Municipal Government will conduct a massive information campaign not only among barangay officials but also among their constituents. Using various possible means of information campaigns such as symposia, consultations, and the like will be most helpful and tenable. The Municipal Government has to greatly consider the establishment of a dumping site and to establish a proper disposal of waste where segregation and recovery of recyclable materials are practiced. Since it is through the recovery facility that the economic activity in garbage sprouts, the strategy is likewise viewed as a potent means in meeting hard-on the problems of Solid Waste Management. Further the following study has to be undertaken, viz. : 1. Investigation on the possible economic return of material recovery facility. 2. Investigation and study on the cultural influence vis-a-vis waste disposal.
Research Paper (P299-Research Methods in Planning). -- Iloilo City : UPV-[CM], October 2005.